R-loopDB: a database for R-loop forming sequences (RLFS) and R-loops - Jenjaroenpun, Piroon (2017)
R-loopDB (http://rloop.bii.a-star.edu.sg) was originally constructed as a collection of computationally predicted R-loop forming sequences (RLFSs) in the human genic regions. The renewed R-loopDB provides updates, improvements and new options, including access to recent experimental data. It includes genome-scale prediction of RLFSs for humans, six other animals and yeast. Using the extended quantitative model of RLFSs (QmRLFS), we significantly increased the number of RLFSs predicted in the human genes and identified RLFSs in other organism genomes. R-loopDB allows searching of RLFSs in the genes and in the 2 kb upstream and downstream flanking sequences of any gene. R-loopDB exploits the Ensembl gene annotation system, providing users with chromosome coordinates, sequences, gene and genomic data of the 1 565 795 RLFSs distributed in 121 056 genic or proximal gene regions of the covered organisms. It provides a comprehensive annotation of Ensembl RLFS-positive genes including 93 454 protein coding genes, 12 480 long non-coding RNA and 7 568 small non-coding RNA genes and 7 554 pseudogenes. Using new interface and genome viewers of R-loopDB, users can search the gene(s) in multiple species with keywords in a single query. R-loopDB provides tools to carry out comparative evolution and genome-scale analyses in R-loop biology.